New Method for Calculating Soil Pressure on Shallow Underground Structures in Layered Soil - Pan, Yingdong; Zhou, Xiaojun; Han, Shi; Zhang, Lu; Cui, Pengbo (Geotechnical and geological engineering, 2024)
To calculate the surrounding soil pressure applied to shallow underground structures in layered soils, a new calculation method suitable for shallow underground works in layered soil is proposed by introducing the horizontal slice method (HSM). Through comparison with traditional methods and measured data, the rationality and accuracy of the proposed method are demonstrated. Model parameters, model assumptions, and limitations of the proposed method are also discussed. The research results find that the vertical soil pressure obtained from the proposed method is close to the results of Bierbaum’s theory and method in the Chinese “ Code for Design of Railway Tunnel ”, all showing a linear growth trend, but the lateral earth pressure derived from the proposed method shows a nonlinear distribution. The vertical pressure is linearly positively correlated with internal friction angle, cohesion, and burial depth, while it is linearly negatively correlated with the equivalent friction angle. The lateral earth pressure decreases with an increase in the internal friction angle and cohesion at the same depth, while it increases with an increasing equivalent friction angle. For layered soil, lateral stress undergoes abrupt changes of different degrees at the soil layer boundary and the burial depth boundary.